PROFIL PENDUDUK TERKONFIRMASI POSITIF COVID-19 DAN MENINGGAL: KASUS INDONESIA DAN DKI JAKARTA - Deny Hidayati (Jurnal Kependudukan Indonesia, 2020)
This paper discusses the population that confirmed positive for COVID-19 and died in Indonesia and DKI Jakarta, which is epicentre of corona virus transmission in this country. The trend of population confirmed positive COVID-19 continues to increase and fluctuate every day, while the percentage of population deaths tends to decline. The paper using secondary data revealed that male residents were more vulnerable to COVID-19 than women. The number of male population confirmed positive corona virus is higher and the percentage of death is much higher. Covid-19 attacks all age groups, but the population is over 46 years, especially 60 years and above, more vulnerable than other age groups. Infants, toddlers and children who are detected positively have a low percentage, but the quantity is quite large. The population risk reduction policy for COVID-19 is indispensable for all residents with priority given to more vulnerable groups in Indonesia and DKI Jakarta.